Associated Factors with Pain and Disability in Patients With Knee Osteoarthritis - Duygu Geler Külcü,; Burcu Yanık,; Hakan Atalar,; Gülçin Gülşen, (Archives of Rheumatology, 2010)
Objective: To assess factors associated with pain and functional level in patients with knee osteoarthritis (OA). Materials and Methods: Patients with knee OA (n=161), with a mean age of 62.4± 8.7 yrs were studied. Age, sex, body mass index (BMI), education level, smoking habit, regular physical activity habit, symptom duration were recorded. Kellgren-Lawrence scores were calculated in anterio-posterior and lateral knee radiographs. Functional level of patients were assessed by Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and pain severity of the patients were assessed by Visual Analoge Scale (VAS). Results: The BMI was positively correlated with mean scores of WOMAC pain, joint stiffness and daily living activities subscores (r=0.592, r=0.634, and r=0.749, respectively). Education level was inversely correlated with mean scores of WOMAC pain, joint stiffness and daily living activities subscores (r=-0.394, r=-0.345, and r=-0.352, respectively). Kellgren-Lawrence scores of anterior-posterior and lateral view radiographs were found to be correlated with age and symptom duration (r=0,263, p=0,001 and r=0,339, p=0,016, respectively). No relationship was found between pain VAS scores and any assessed factors.When WOMAC subscale scores and VAS scores were compared according to gender, WOMAC pain scores were found higher in females (p=0.024). No correlation was found between remainder factors and scores of the three sections of WOMAC. Conclusion: The BMI is the most important factor associated with functional level and pain severity of patients with KOA. Patients must be encouraged to loose weight in order to decrease symptom and disease severity. (Turk J Rheumatol 2010; 25: 77-81)